Dinamika Moderasi Umat Islam di Aras Lokal: Interaksi NU, Muhammadiyah, dan LDII, di Kabupaten Lamongan - M. Najib Tsauri; Hamid Nasuhi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2025)
This study examines the practice of Islamic moderation in Kendalkemlagi Village, Karanggeneng Subdistrict, Lamongan Regency, which is inhabited by three major Islamic organizations: Nahdlatul Ulama (NU), Muhammadiyah, and the Indonesian Islamic Da’wah Institute (LDII). The harmonious relations among these groups, despite their differing religious orientations, present an important phenomenon amid ongoing issues of social fragmentation among Islamic organizations in Indonesia. The aim of this research is to describe the forms of religious moderation practiced in the community and to analyze the social factors that support the creation of harmony at the local level. This study employs a qualitative research design using a sociology of religion approach. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using Joachim Wach’s cross-sectional comparative method and Emile Durkheim’s concept of social cohesion. The findings reveal that religious moderation in Kendalkemlagi is manifested through inter-organizational cooperation in socio-religious activities, inter-affiliational kinship ties, and an inclusive tradition of village deliberation. Local values such as gotong royong (mutual cooperation) and a strong sense of belonging reinforce social integration within the community. In conclusion, religious moderation in Kendalkemlagi is a social construct shaped by inclusive cultural and religious interactions, providing a concrete model of moderate Islam practiced at the grassroots level.